2016
DOI: 10.3847/0004-637x/830/1/1
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Kepler Habitable Zone Exoplanet Candidates

Abstract: The NASA Kepler mission has discovered thousands of new planetary candidates, many of which have been confirmed through follow-up observations. A primary goal of the mission is to determine the occurrance rate of terrestrial-size planets within the Habitable Zone (HZ) of their host stars. Here we provide a list of HZ exoplanet candidates from the Kepler Data Release 24 Q1-Q17 data vetting process. This work was undertaken as part of the Kepler Habitable Zone Working Group. We use a variety of criteria regardin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
150
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 88 publications
2
150
0
Order By: Relevance
“…Discoveries of terrestrial planets in the habitable zone (HZ) by both the Kepler mission and ground-based surveys (Kane et al 2016;Anglada-Escudé et al 2016;Gillon et al 2017) have shown that potentially habitable planets are common in our galaxy (Petigura et al 2013;Foreman-Mackey et a. 2014;Silburt et al 2015;Dressing & Charbonneau 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Discoveries of terrestrial planets in the habitable zone (HZ) by both the Kepler mission and ground-based surveys (Kane et al 2016;Anglada-Escudé et al 2016;Gillon et al 2017) have shown that potentially habitable planets are common in our galaxy (Petigura et al 2013;Foreman-Mackey et a. 2014;Silburt et al 2015;Dressing & Charbonneau 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The source of our target list is an early version of the catalog of small HZ candidates published by Kane et al (2016), which in turn is the product of the efforts by the Kepler HZ Working Group to evaluate the full set of candidates observed during the mission's quarters 1 through 17 (Q1-Q17). This catalog describes the various definitions used by different authors for the HZ and chose to consider both an "optimistic" (larger) HZ and a "conservative" (smaller) HZ, based on the assumptions of Kopparapu et al (2014) informed by estimates of how long Venus and Mars may have been able to retain liquid water on their surfaces.…”
Section: Target Selectionmentioning
confidence: 99%
“…A number of the candidates presented by Kane et al (2016) have been validated by others and have subsequently received official Kepler planet designations. However, in most cases, those validation studies have only been concerned with demonstrating the presence of a planet associated with the target but not necessarily orbiting it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[e.g. [3][4][5] the excellent quality of the photometric data has enabled us to make tremendous progress on the understanding of stellar evolution and dynamics [6][7][8][9][10][11][12][13]. In particular, the mission showed the power of asteroseismology to better constrain the fundamental properties of planet host stars (such as radius and age) needed to characterize planetary systems but also to probe the structure and rotation in deeper layers of stars.…”
Section: Introductionmentioning
confidence: 99%